Nutritional ecology of temperate octocorals in a warming ocean - Lange, Kiara; Maguer, Jean-François; Reynaud, Stéphanie; Ferrier-Pagès, Christine (Frontiers in Marine Science, 2023)
Global warming of the oceans poses a double threat to benthic organisms as they reach their thermal limits and starve to death due to declines in plankton abundance during heat waves. Under these circumstances, dissolved nutrients become an important alternative food source, especially in temperate regions where they can reach high concentrations. Although octocorals play a central role in temperate Marine Animal Forests and benthic-pelagic coupling, our knowledge of their feeding ecology is still limited. We used 13C and 15N isotope labeling to investigate feeding rates on dissolved inorganic (carbon, ammonium, nitrate) and organic (urea, amino acids) nutrients of the two most common Mediterranean gorgonians, the mixotrophic species Eunicella singularis and the heterotrophic species Paramuricea clavata. We also measured the uptake of natural dissolved organic matter (DOM) provided at different concentrations. Measurements were conducted at 17°C and 24°C to anticipate the effects of ocean warming. Our findings indicate that gorgonians exhibit notably low uptake rates of dissolved inorganic and organic nutrients, both at 17°C and 24°C. At 24°C, gorgonians experienced heat stress, as evidenced by elevated respiration rates, the loss of symbionts in E. singularis, and decreased lipid reserves in P. clavata. However, we did not observe a significant increase in the uptake rates of dissolved inorganic or organic nutrients, except for dissolved organic carbon in E. singularis. This study provides valuable insight into the nutritional requirements of temperate octocorals. The results demonstrate that dissolved nutrients, in particular nitrogen, do not play a substantial role in the diet of gorgonians, suggesting that these organisms primarily rely on the capture of plankton and detrital material for their nitrogen requirements. Therefore, temperate octocorals may be at high risk of severe starvation in the future.